DECENT WORK AT LOCAL DIGITAL PLATFORMS IN SERBIA - Kovačević, Aleksandar (Political Review, 2023)
In this study, we examine the concept of decent work on local digital platforms in Serbia. So, this article focuses on the research topic of whether labour done on local digital platforms may be classified as "decent work." Labour digitization and the digital economy are novel phenomena that need in-depth examination. We begin with the concept of the digital economy as a basis for the development and expansion of digital labour. This new economy is characterised by knowledge and the use of various smart tools, as well as the crossing of national borders, and so on. Nowadays, we may talk about the gig economy, which is defined by short-term employment on online platforms or labour via mobile applications. These developments resulted in the establishment and growth of a worldwide digital labour market marked by non-standard forms of employment, insecure labour agreements, and the involvement of third-party intermediaries between employees and clients. There are considerable efforts to alter employment legislation throughout Europe. Co-regulation, which involves several players in the decision-making process, is one possible option. The Directive on Improving Working Conditions in Platform Work, which is now in the process of adoption, is perhaps the most important document at the EU level. It is worth mentioning the practices of the European Union's Court of Justice, national courts in Spain, the Netherlands, Italy, and Germany, as well as national regulations in both Italy and France that establish the right to disconnect. We must also acknowledge the work of international and national trade union federations, such as the European Trade Union Confederation. So, the most pressing issue in this study is finding decent work in the digital labour market. A decent work index comprises many indicators. With statistical and legal indicators, the International Labour Organisation discusses 10 core aspects of decent work. According to an early study, there is no decent work on digital platforms due to bogus self-employment, which occurs when certain entrepreneurs work for only one company. The reasons for this phenomenon are reduced expenses and employers' lack of accountability. This is also an aspect of digital labour in Serbia. To assess the gig economy in Serbia, we use the online labour index and the gigmeter. According to the online labour index, Serbia is among the top 15 nations in the world in terms of the number of digital employees, accounting for 1.4% of the global total. Software development is the most frequent occupation. According to the gigmeter, the most frequent employment is creative and multimedia. The most crucial duty is to figure out how many digital employees there are in Serbia. According to the most conservative estimate, Serbia has almost 90,000 digital employees. Almost two-thirds of digital employees in Serbia are in hidden employment. Now we can talk about doing decent work on digital platforms in Serbia. To assess decent work, we apply the Fair Work Principles. Fair pay, fair conditions, fair contracts, fair management, and fair representation re among these principles. Every platform can be scored with a basic and an extra point, for a total of 10 points. The study incorporates five platforms: Uradi-zaradi, Glovo, Wolt, Car: Go, and Mr.D. According to the Fairwork rating, Uradi-zaradi and Wolt met the most requirements but received just a passing grade. The Public Policy Centre performed extensive research on decent work to find that it does not exist on digital platforms. The most essential motivation for digital labour is a high wage, which comes at the price of a long working week. This study determined that neither platform satisfies the passing standard and makes some recommendations for improving working conditions on local platforms. First, the practice of bogus self-employment must be stopped. Second, labour legislation must be revised. Third, the right to collective bargaining must be extended to digital workers. This can be done by a strong trade union movement that can find a way to safeguard digital employees without jeopardising traditional workers' rights.
Keywords: labour digitalization; digital economy; local digital platforms; decent work